2017
DOI: 10.1111/ppa.12755
|View full text |Cite
|
Sign up to set email alerts
|

Meloidogyne luci, a new root‐knot nematode parasitizing potato in Portugal

Abstract: In 2013, during a field survey conducted in Portugal on potato, Solanum tuberosum, an unusual esterase (EST) phenotype was detected in a root‐knot nematode (RKN) from potato roots collected in Coimbra. This Portuguese isolate was purified and maintained on tomato, S. lycopersicum, and morphological, biochemical and molecular characteristics were studied. Perineal pattern morphology was highly variable, similar to Meloidogyne ethiopica and not useful for identification. The EST phenotype, from young egg‐laying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 25 publications
3
54
0
1
Order By: Relevance
“…, ), 25 of which have been found in Europe (Wesemael et al , ; Archidona‐Yuste et al , ; Santos et al , ). In Portugal, eight RKN species ( M. arenaria , M. chitwoodi , M. hapla , M. hispanica , M. incognita , M. javanica , M. luci and M. lusitanica ) have been found parasitizing several economically important crops (Pais & Abrantes, ; Abrantes & Santos ; Abrantes et al , ; Conceição et al , ; Esteves et al , ; Maleita et al , ). Typically, M. arenaria , M. incognita , M .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ), 25 of which have been found in Europe (Wesemael et al , ; Archidona‐Yuste et al , ; Santos et al , ). In Portugal, eight RKN species ( M. arenaria , M. chitwoodi , M. hapla , M. hispanica , M. incognita , M. javanica , M. luci and M. lusitanica ) have been found parasitizing several economically important crops (Pais & Abrantes, ; Abrantes & Santos ; Abrantes et al , ; Conceição et al , ; Esteves et al , ; Maleita et al , ). Typically, M. arenaria , M. incognita , M .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Meloidogyne genus comprises more than 100 described species (Moens et al, 2009), 25 of which have been found in Europe (Wesemael et al, 2011;Archidona-Yuste et al, 2018;Santos et al, 2019). In Portugal, eight RKN species (M. arenaria, M. chitwoodi, M. hapla, M. hispanica, M. incognita, M. javanica, M. luci and M. lusitanica) have been found parasitizing several economically important crops (Pais & Abrantes, 1989;Abrantes & Santos 1991;Abrantes et al, 2008;Conceic ßão et al, 2009;Esteves et al, 2015;Maleita et al, 2018). Typically, M. arenaria, M. incognita, M. javanica and M. hapla are considered the most widespread and damaging, often classified as major RKN species (Moens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that there is no known differential host plant found so far to distinguish between M. ethiopica and M. luci suggests that the two species are very closely related (Geri c Stare et al, 2017). Meloidogyne luci has already been detected in open field agricultural production in Europe as it has been found in kiwi and maize production in Greece (Conceic ßão et al, 2012) and potato production in Portugal (Maleita et al, 2017). Therefore M. ethiopica (Carneiro et al, 2003(Carneiro et al, , 2007Aballay et al, 2009;Medina et al, 2014) as well as M. luci (Maleita et al, 2017) represent a serious threat to agriculture.…”
Section: Potential Threat For the Eppo Regionmentioning
confidence: 97%
“…Meloidogyne luci has a very wide host range of monocotyledons and dicotyledons, including important agricultural crops such as maize, potatoes and variety of vegetables (Strajnar et al, 2009;Maleita et al, 2017). Meloidogyne luci has a very wide host range of monocotyledons and dicotyledons, including important agricultural crops such as maize, potatoes and variety of vegetables (Strajnar et al, 2009;Maleita et al, 2017).…”
Section: Potential Threat For the Eppo Regionmentioning
confidence: 99%
See 1 more Smart Citation